A cohort study on anxiety and perceived recovery 3 and 12 months after mild to moderate stroke - Nelsone, Linda; Rafsten, Lena; Abzhandadze, Tamar; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2023)
Background Anxiety is a common complication of stroke, affecting one in every three stroke survivors. Stroke recovery is a dynamic process, with most recovery occurring within the first 3 months. However, how anxiety affects this dynamic remains unknown. Therefore, this study aimed to investigate how anxiety affects perceived recovery at 3 and 12 months after stroke. Additionally we also examined the change in perceived stroke recovery from 3 to 12 months and its relationship with anxiety. Methods In this longitudinal study patients with stroke were enrolled at Sahlgrenska University Hospital, Gothenburg, Sweden. The Hospital Anxiety and Depression Scale was used to assess anxiety, and the Stroke Impact Scale was used to assess perceived recovery 3 and 12 months after the stroke. The difference in perceived stroke recovery between the anxiety and no-anxiety groups at 3 and 12 months was analyzed. Changes in perceived stroke recovery were calculated and trichotomized from 3 to 12 months based on clinically significant positive changes (+10 points or more), clinically important negative changes (−10 points or less), or no changes (±9). At 3 and 12 months after the stroke, negative and positive recovery was compared to no change in recovery regarding anxiety scores. Results This study included 99 patients (44.4% female, median age, 77 years). At 3 and 12 months after the stroke, the median recovery score was 80 out of 100. At 3- and 12-months 17.6 and 15.7% of the patients experienced anxiety, respectively. At both time points, there was a significant association between anxiety and lower perceived stroke recovery (at 3 months: p < 0.001; and 12 months p = 0.002). Among participants with anxiety at 3 or 12 months after stroke, a positive change in recovery from 3 to 12 months was identified (3 months, p = 0.004 and 12 months, p = 0.0014). Conclusion Anxiety symptoms following a stroke are associated with lower levels of perceived stroke recovery for at least 1 year after the stroke. Identifying patients with anxiety early after stroke may be beneficial for identifying those at risk of lower recovery. Clinical trial registration:ClinicalTrials.gov, identifier [NCT01622205]. Registered on June 19, 2012 (retrospectively registered).